Crowdsourcing as a method of obtaining information - Natalia Przybylska (Foundations of Management, 2013)
The aim of this article is to analyse and describe a new trend in obtaining information and solving problems, which is crowdsourcing. Contemporary enterprises face enormous challenges, which are connected with omnipresent changes occurring in the functioning of societies and economies all over the world. Crowdsourcing is a very complex and constantly evolving phenomenon. It is an open subject of multiple discussions in which, due to its multiple factors and variable applications, it is being differently defined. Growing usage of this phenomenon prompts scientists for undertaking research and analysis of this issue as it is strictly connected with dynamically changing attitudes of, not only, entrepreneurs, but also their surroundings. The prime driving force behind undertaking this subject is a fast development of technology, Web 2.0, or globalisation. The mechanism of crowdsourcing's functioning has been known for ages; however, it was named as a tool for modern enterprises 10 years ago. During that short period of time crowdsourcing has gained the acceptance of a number of people all over the world. The challenge for the present research is, as well, to indicate advantages and underline the essence of proper managing of crowdsourcing in enterprises, what involves a number of aspects. The described solution is still gaining more and more proponents; however, planned inappropriately, may cause completely reversible effect than the desired one. In this article, descriptions of worldwide ventures, which apply crowdsourcing, in Poland as well, and the results of the newest research on the phenomenon were included.
Keywords: 650; crowdsourcing; innovations; Web 2.0; prosumerism; outsourcing